Geoconservation of Vertebrate and Human Ancient Fossils Site, The South TulungagungArea East Java - Setiyabudi, Erick; Trihascaryo, Agus; Koesbarditi, Tutik; Adi Suriyanto, Rusyad; Bayu Murti, Delta (Jurnal Geologi dan Sumberdaya Mineral, 2019)
The paleontology and archeology sites in southern Tulungagung, East Java are part of the geodiversity and geological heritage that has significance for the process of evolution and migration of early modern humans. The sites are Wajak Cave, Song Gentong, and Tenggar Cave (Late Pleistocene to Early Holocene) located in the marble and limestone ornaments mining area of the Campurdarat Formation. Geoconservation of the geological heritage continues to be carried out by research or excavation in these fossil sites to reveal the past life and paleoenvironment, where the fossil site is susceptible to the threat of damage due to surrounded mining activities.Keyword: Wajak Cave, Song Gentong, Tenggar Cave, limestone, marble, Campurdarat Formation.